An introduction to the law of contract - Stephen Graw (Thomson, 2005)
An Introduction to the Law of Contract remains a highly successful, easy to read, easy to understand textbook for students encountering the law of contract for the first time. This edition brings its coverage completely up-to-date and includes references to all of the major caselaw and legislative changes that have occurred since 2014. The major new cases covered include: The High Court’s decisions in Paciocco v ANZ Banking Group (penalties and unconscionability), Mount Bruce Mining Pty Limited v Wright Prospecting Pty Limited (construction of contracts), Crown Melbourne Ltd v Cosmopolitan Hotel (Vic) Pty Ltd (promissory estoppel and collateral contracts), Simic v New South Wales Land and Housing Corporation (rectification and ‘continuing common intention’) and Gynch v Polish Club Ltd (illegality); Mainteck Services Pty Ltd v Stein Heurtey SA, Essential Beauty; Franchising (WA) Pty Ltd v Pilton Holdings Pty Ltd and Technomin Australia Pty Ltd v Xstrata Nickel Australasia Operations Pty Ltd (ambiguity); Baldwin v Icon Energy Ltd and Mushroom Composters Pty Ltd v IS &​ DE Robertson Pty Ltd (good faith); Vantage Systems Pty Ltd v Priolo Corporation Pty Ltd, Ailakis v Olivero (No 2), Arfaras v Vosnakis and Smilevska v Smilevska (No 2) (intention to be bound) Hawcroft v Hawcroft General Trading Co Pty Ltd, HWG Holdings Pty Ltd v Fairlie Court Pty Ltd and Menegazzo v PricewaterhouseCoopers (mistake); and Arab Bank Australia Ltd v Sayde Developments Pty Ltd and Stoyanova v Equity-One Mortgage Fund Ltd (penalties) The legislative changes referred to include, in particular, the amendments to the Australian Consumer Law’s unfair contract terms provisions, which were extended to include ‘small business contracts’ as well as the ‘consumer contracts’ to which they had previously applied. An Introduction to the Law of Contract, 9th Edition continues to be a valuable resource for all students undertaking contract law at undergraduate level and is, especially, essential reading for accounting, business and commerce students."--Back cover.